Islam, Radicalism, and the Politics of Refusal: FPI’s “Making Do" With the Vaccine Program (2020-2022) - Awalia Rahma; Nurul Hayati; Tati Rohayati (Buletin Al-Turas, 2026)
Purpose This study investigated COVID-19 vaccine hesitancy among members of the Islamic Defenders Front (FPI) during the 2020-2022 pandemic through Michel de Certeau's conceptual lens of "making do" (la perruque) and everyday tactics. Method Employing historical methods—including source criticism and oral history—primary sources were collected through interviews with FPI members from grassroots levels to field commanders, supplemented by analysis of social media narratives and contemporary news reports. Data were analyzed using thematic analysis informed by de Certeau's framework.  Result/Findings The findings revealed that vaccine decisions made up tactical maneuvers rather than mere ideological rejection. Conditional acceptance—choosing Moderna over Sinovac, awaiting MUI fatwas, or complying only when workplace requirements demanded—exemplifies de Certeau's concept: practices that appear compliant while preserving autonomy. Active refusal manifested through creative circumvention, such as avoiding vaccine-mandated public transportation or sustaining alternative narratives amid official campaigns. The absence of clear directives from Habib Rizieq Shihab created space for diverse individual tactics.  Conclusion This study concluded that FPI members "make do" by negotiating state authority using conditional compliance and active circumvention. This transformation causes public health interventions go beyond correcting disinformation and instead address the cultural frameworks and systemic skepticism that underpin these individual moves